Microsimulation of tax-benefit systems in the Global South: A comparative assessment - Jesse Lastunen; Antoine de Mahieu; Katrin Gasior; H. Xavier Jara; Jukka Pirttilä (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
This paper analyses the effectiveness of tax-benefit systems in reducing poverty and inequality across 13 countries in the Global South. Using national survey data and tax-benefit microsimulation models from the SOUTHMOD project, we provide a cross-country perspective on the redistributive impact of fiscal policies. Our analysis involves decomposing the sources of disposable income across the income distribution and estimating the contributions of different policy instruments to poverty and inequality. Additionally, we assess gender disparities in outcomes, quantify the distributional effects of recent policy changes, and simulate two budgetneutral tax-benefit reforms, focusing on their targeting efficiency and effects on work incentives. Studying the variability of these effects across countries illustrates how better policy design can improve welfare outcomes.
Keywords: D31; H23; I38; J22; 330; tax-benefit systems; microsimulation; poverty; inequality; social protection; gender; work incentives